Thermally annealed self-assembled three-dimensional graphene for direct construction of porous flow distributor in polymer electrolyte membrane fuel cell. (26th October 2021) - Lee, Gil Won; Seol, Changwook; Kim, Koung Moon; Lim, Sun Taek; Shim, Gyu Hyeon; Kim, Sang Moon; Ahn, Ho Seon
Abstract: Self-assembled three-dimensional graphene (STG), which is constructed via advanced boiling method (ABM) has advantages in terms of low-cost, facile procedures, and needless to use any backbone structure. Although the previously developed STG is considered as a promising material and structure to be used as a flow distributor in polymer electrolyte membrane fuel cell (PEMFC), the STG flow distributor should be advanced in the aspect of conductivity to achieve higher performance. Herein, the conductivity of STG is improved via the thermal annealing process and the advanced STG is applied in PEMFC as a flow distributor to enhance the performance of the single-cell system. Single cell constructed with the thermally annealed STG exhibits a lowered charge and ohmic resistance, which leads to the performance enhancement. These results imply that direct coating of the advanced STG can be one of the alternatives of the complex and high-cost process of graphene coating to the porous metal foam through chemical vapor deposition (CVD). Highlights: The conductivity of STG flow distributor is improved via thermal annealing process. Advanced STG flow distributor leads to the enhanced performance of PEMFC system. Thermal annealing to STG is effective for lowering ohmic & kinetic resistances. Advanced STG shows remarkable potential for replacing CVD-based 3D graphene.